Ports into the next century proceedings of the conference UK ports 2000 organized by the Institution of Civil Engineers and held in Hull on 17-18 October 1990. (Thomas Telford, 1991)
Industry professionals from all aspects of port administration design and operation, together with consultants from Customs and Excise, the fishing industry and engineering profession, present the issues concerning the future of ports.